The parolee-parole officer relationship as a mediator of criminal justice outcomes - Blasko, Brandy L. (Criminal justice and behavior, 2015)
Although psychotherapy literature identifies the client?therapist relationship as a key factor contributing to client outcomes, few studies have examined whether relationship quality among corrections populations and supervising officers influences outcomes. This is surprising given that many criminal justice intervention models include quality of the client?practitioner relationship. Parolees enrolled in a six-site randomized clinical trial, where they were assigned to a parole officer?therapist?client collaborative intervention designed to improve relationship quality (n = 253) or supervision as usual (n = 227), were asked to rate relationship quality with their supervising officer. Results showed parolees assigned to the intervention endorsed significantly higher relationship ratings and demonstrated a lower violation rate than those assigned to the control group. Ratings of the parolee?parole officer relationship mediated the relationship between study condition and outcomes; better perceived relationship quality was associated with fewer drug use days and violations during the follow-up period, regardless of the study condition. Findings are discussed as they pertain to supervision relationships.